The relationship of parent parenting patterns with temper tantrum behavior in pre-school age children in tualang village, kec. Siempat nempu hulu kab. From sidikalang in 2021 - Ance Siallagan; Friska Ginting; Niko Simamora (Jurnal EduHealth, 2022)
Pre-school age children in their growth and development experience many changes, both physical and mental changes. This is where the role of parents is needed, because in this preschool period the child's character and behavior are formed. However, many parents follow the requests of the child too much, so that the child gets what he wants, and when one day the parents are unable to fulfill his request, the child can have a tantrum. Tantrums are episodes of peak anger that are usually described by rolling crying, and extreme frustration, because it can hurt the child. Temper tantrums are strongly influenced by parenting patterns, the way parents raise their children plays a role in causing tantrums. Parents who dominate children, fathers and mothers who disagree, and inconsistent parenting causes temper tantrums. The purpose of this study was to identify the relationship between parenting and temper tantrum behavior in preschool children in Tualang Village, Kec. Siempat Nempu Hulu, Kab. Dairi, Sidikalang. This research method uses a correlation design with a sample of 40 respondents in Tualang Village, Kec. Siempat Nempu Hulu. The measuring instrument used in this study was a parenting style questionnaire and a temper tantrum behavior questionnaire. Data analysis was carried out using the chi square test with (p = 0.015). The results of this study indicate that there is a relationship between parenting patterns and temper tantrum behavior in pre-school age children in Tualang Village, Kec. Siempat Nempu Hulu, Kab. Dairi, Sidikalang..